2015
DOI: 10.1007/s40846-015-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Motion Tracking Using Acromion Skin Marker Cluster: In Vitro Accuracy Assessment

Abstract: Several studies have recently investigated how the implementations of acromion marker clusters (AMCs) method and stereo-photogrammetry affect the estimates of scapula kinematics. However, in the large majority of these studies, the accuracy assessment of the scapular kinematics obtained with AMCs was carried out through a comparative evaluation using a scapula locator that is prone to error. The present study assesses AMC accuracy based on best practice recommendations, both with single and double anatomical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…We did not find a significant effect of double calibration for anterior tilt and lateral rotation, although increased lateral rotation was measured above 90°AB (10-14°, P 40.06). The different findings might be due to the study population (young healthy subjects with low variability (Brochard et al, 2011) and cadaveric specimen without shoulder damage (Cereatti et al, 2015) versus patients with shoulder pathology with high variability). Furthermore, in the set-up of (Brochard et al, 2011) and (Cereatti et al, 2015) the skin-fixed markers were placed on a different position on the scapula, i.e.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…We did not find a significant effect of double calibration for anterior tilt and lateral rotation, although increased lateral rotation was measured above 90°AB (10-14°, P 40.06). The different findings might be due to the study population (young healthy subjects with low variability (Brochard et al, 2011) and cadaveric specimen without shoulder damage (Cereatti et al, 2015) versus patients with shoulder pathology with high variability). Furthermore, in the set-up of (Brochard et al, 2011) and (Cereatti et al, 2015) the skin-fixed markers were placed on a different position on the scapula, i.e.…”
Section: Discussionmentioning
confidence: 89%
“…Brochard et al (2011) showed that when using optical markers for scapular kinematic measurement, double calibration with a scapula locator mainly affected the measure of anterior tilt and lateral rotation at high elevation angles. Also Cereatti et al (2015) showed that double calibration improved scapular kinematics (up to 14°). We did not find a significant effect of double calibration for anterior tilt and lateral rotation, although increased lateral rotation was measured above 90°AB (10-14°, P 40.06).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations